Comparisons between elastographic stiffness scores for benign versus malignant lymph nodes in dogs and cats. Issue 1 (6th September 2017) - Seiler, Gabriela S.; Griffith, Emily
Abstract: Lymph node evaluation is an important component of oncology staging in dogs and cats, however diagnosis of malignancy currently requires cytology or histopathology. Elastography is an ultrasound technique that allows estimation of tissue stiffness. In people, it has been shown to increase the sensitivity of sonography in detection of metastatic lymph nodes. The objective of this prospective, cross‐sectional study was to determine if elastographic stiffness differs for malignant versus benign canine and feline lymph nodes that were considered abnormal in gray‐scale ultrasound imaging. Animals scheduled for ultrasound‐guided fine needle aspirates of a lymph node at a single center were prospectively enrolled. Elastography was performed by a board‐certified veterinary radiologist (G.S.) prior to tissue sampling. Softness was scored qualitatively as 1–4 (1 = hard; 4 = soft) on an image depicted by a color scale (blue = hard, red = soft). Quantitative analysis was performed using custom‐made software. Fifty‐one lymph nodes were included in the evaluation, 21 had benign and 30 had neoplastic cytology. Benign lymph nodes were softer (median score of 2.5, range 1–4) than malignant lymph nodes (median = 2, range 1–3), and differences were significant in qualitative and quantitative analyses ( P  < 0.01). Of the lymph nodes with a score of 2 or below (hard), 19/25 (76%) were malignant, of the lymph nodes with a score over 2 (soft), 24/36 (67%) were benign. Findings indicated that elastographic stiffness scores differed between benign and malignant lymph node groups; however overlapping scores for the two groups limited the use of this technique for routine clinical diagnosis of malignancy.